The Anterolateral Complex of the Knee. Issue 4 (27th April 2017) - Herbst, Elmar; Albers, Marcio; Imhoff, Andreas; Fu, Freddie; Musahl, Volker
Aims and Objectives: : The objective of this study was to clarify the layer-by-layer anatomy of the anterolateral complex of the knee. Materials and Methods: : Twenty fresh-frozen human cadaveric knees (age range 38 - 56 yrs.) without any history of knee injury or surgery were used for this dissection study. After skin and subcutaneous tissue removal, the ITB was incised in its most anterior part and reflected posteriorly followed by blunt dissection of its deeper layers. Subsequently, an incision was made between the ITB and the short head of the biceps muscle with consecutive evaluation of the insertion site of the biceps tendon and its extensions. Once the deep layers of the ITB were identified, the connections to the lateral intermuscular septum and Kaplan fibers were cut. The superficial ITB was then reflected distally in order to assess the geographical relationship between the superficial and deep ITB as well as the distal anteromedial aspect of the biceps muscle. Finally, the anterolateral capsule was incised to evaluate its connections to the surrounding anatomic structures. Results: : The anterolateral aspect of the knee consists of three distinct layers. Superficially, the ITB with its insertion to Gerdy's tubercle and extensions to the patella (iliopatellar band) was appreciated. Posterior reflection of the superficial ITB revealed a firm distinct connection of Kaplan fibers to the distal femoral metaphysis. The deep layer of the ITB runs from the Kaplan fibers in a distal direction and forms a functional arc. This arc is reinforced by the capsulo-osseous layer of the ITB, which originates from an area distal to the Kaplan fibers, the fascia of the lateral gastrocnemius and plantaris muscles. The distal half of the capsulo-osseous layer merges posteriorly with the fascia of the biceps muscle. The three layers of the ITB become confluent distally. Its insertion spanned from Gerdy's tubercle to an area just posteriorly, with the capsulo-osseous layer forming the posterior part. The biceps muscle has fascial and aporoneurotical extensions, which insert to the proximal tibia together with the capsulo-osseous layer of the ITB. Layer 3 consists of the anterolateral capsule. In 7/20 (35%) specimens the mid-third capsular ligament was observed as a thickening within, but not separate from the anterolateral capsule. Conclusion: : The anterolateral complex of the knee consists of the ITB with its three layers, the functional arc formed by the fibers between the distal femoral metaphysis and Gerdy's tubercle, and the anterolateral capsule. In 35% of specimens a capsular thickening (mid-third capsular ligament) was identified. Surgeons should consider the complex anatomy of this functional unit, i.e. the anterolateral complex, when considering lateral extra-articular procedures.